Inequality of Thought (IOT) on HIV-Aids and LGBT Through Social Media: A Case Study Gen Z in JPC Foundation - Erlina Puspitaloka Mahadewi; Mohamad Reza Hilmy; Puspita Chairun Nisa; Ario Pamungkas; Suryari Purnama; Mehmet Ozays; Sundring Pantja Djati (International Journal of Health and Pharmaceutical (IJHP), 2025)
The study focused on the purpose of finding out the effect and covering the views and acceptance of LGBT. Jakarta Indonesia is beginning to be seen clearly, especially the large amount of LGBT content both on television stations and on social media at home and abroad. This is very worrying because shows that LGBT is a risk factor for sexually transmitted infections (STIs) including HIV/AIDS. Unsafe sex, drugs, and many sexual partners, make LGBT people more susceptible to STIs. This study aims to determine the description of knowledge about STIs and attitudes towards the LGBT phenomenon in society, especially among young Gen Z people who still have the impact of inequality of thinking in social media. This study is a qualitative descriptive study conducted from October to December 2024. Data collection used a google form questionnaire. The sample consisted of 75 respondents who were members of the community fostered by the "Jakarta Plus Center (JPC)" Foundation. The sampling technique used was purposive sampling. The data is presented in a frequency table. The results of this study showed that most respondents had good general knowledge about STIs but lacked in more specific knowledge questions in medicine. The acceptance and views of the community in this community towards the LGBT phenomenon are quite low. People in the community consider LGBT to have a negative impact on life, although respondents agree that the human rights of LGBT people as humans must still be protected and respected, as they see on social media.